Crowd Detection, Monitoring and Management : A literature Review - Sa’ad, Hisham Haider Yusef; Al-Ashmoery, Yahya; Haider, Adnan; Al-Marhabi Zaid; Kaleed Alwasbi; Ruqaih Hussein Salman (Journal of Amran University, 2023)
The rapid increase in the global population has led to the emergence of large crowds during public events across various domains such as sports, music festivals, religious gatherings, and political campaigns. If these events are not properly organized and controlled, they have the potential to result in disasters. Tragically, stampedes occur every year, causing fatalities, disappearances, and injuries for many individuals. Therefore, crowd identification, monitoring, and control are problems that will be addressed and discussed in this paper in order to lessen casualties and prevent such catastrophes. The objective of this study is to present a thorough review of technologies and methods relevant to crowd management, planning, behaviour analysis, and counting. Furthermore, it aids researchers' future progress by examining recent technology developments in the field of crowd planning and monitoring.